Conditional contracts in indirect local procurement of maize from smallholder farmers in Uganda: A study design to assess impacts - Raghunathan, Kalyani; Abate, Gashaw T.; Van Campenhout, Bjorn; Nabwire, Leocardia; Mukangabo, Emerence; Mugabo, Serge; Benin, Samuel (International Food Policy Research Institute, 2025)
Improving smallholder farmers’ access to reliable markets can have significant impacts on their wellbeing, income, poverty reduction, dietary diversity, and rural economic growth. As the choice of marketing channels may influence outcomes differently depending on the context, a key issue is understanding the effectiveness of different marketing instruments. One such modality is a conditional contract between a buyer and the traders supplying it. Such a contract requires traders to source a certain percentage of their supplies directly from smallholder farmers. This raises the question of whether conditional contracts create access to reliable markets for smallholder farmers, result in value chain transformation, and sustain market engagement between traders and smallholder farmers.